Crash inquiry chief promises change. - The Sun, Alyaa Alhadjri (2011)
PETALING JAYA: Once cannot blame the public for being sceptical over the setting up of yet another panel of inquiry to investigate a major fatal accident.But Prof Datuk Radin Umar Radin Sohadi(pix) believed that the panel set up last week to probe the Dec 20 Simpang Pulai-Cameron Highlands express bus crash will be different.